Networked microcontrollers for accessible, distributed spatial audio - Rushton, Thomas Albert; Michon, Romain; Serafin, Stefania; Risset, Tanguy; Letz, Stéphane (Frontiers in Virtual Reality, 2024)
State-of-the-art systems for spatial and immersive audio are typically very costly, being reliant on specialist audio hardware capable of performing computationally intensive signal processing and delivering output to many tens, if not hundreds, of loudspeakers. Centralised systems of this sort suffer from limited accessibility due to their inflexibility and expense. Building on the research of the past few decades in the transmission of audio data over computer networks, and the emergence in recent years of increasingly capable, low-cost microcontroller-based development platforms with support for both networking and audio functionality, we present a prototype decentralised, modular alternative. Having previously explored the feasibility of running a microcontroller device as a networked audio client, here we describe the development of a client-server system with improved scalability via multicast data transmission. The system operates on ubiquitous, commonplace computing and networking equipment, with a view to it being a simple, versatile, and highly-accessible platform, capable of granting users the freedom to explore audio spatialisation approaches at vastly reduced expense. Though faced by significant technical challenges, particularly with regard to maintaining synchronicity between distributed audio processors, the system produces perceptually plausible results. Findings are commensurate with a capability, with further development and research, to disrupt and democratise the fields of spatial and immersive audio.